The Terror - Bird Trap - Cole, Steve; Fox, Woody (ill) (London : Red Fox, 2006)
On the planet Atlantos, two dino-tribes are on the verge of war! Hurrying to save the day, the astrosaurs find monster-sized birds on the schene -- but are they there to help or to make things worse? Teggs must learn the truth before a terrible trap closes around them all ..
Keywords: Children's Literature : Fiction